Tony Atkinson and his legacy - Rolf Aaberge; François Bourguignon; Andrea Brandolini; Francisco H. G. Ferreira; Janet C. Gornick; John Hills; Markus Jäntti; Stephen P. Jenkins; Eric Marlier; John Micklewright; Brian Nolan; Thomas Piketty; et al. (Statistics Norway, Research Department, 2017)
Tony Atkinson is universally celebrated for his outstanding contributions to the measurement and analysis of inequality, but he never saw the study of inequality as a separate branch of economics. He was an economist in the classical sense, rejecting any sub-field labelling of his interests and expertise, and he made contributions right across economics. His death on 1 January 2017 deprived the world of both an intellectual giant and a deeply committed public servant in the broadest sense of the term. This collective tribute highlights the range, depth and importance of Tony's enormous legacy, the product of over fifty years' work.
Keywords: 330